SURGICAL SITE INFECTION IN ORTHOPEDIC IMPLANTS AND ITS COMMON BACTERIA WITH THEIR SENSITIVITIES TO ANTIBIOTICS, IN OPEN REDUCTION INTERNAL FIXATION - Shah, Muhammad Qaisar; Zardad, Muhammad Shoaib; Khan, Alamzeb; Ahmed, Sajjad; Awan, Abdus Saboor; Mohammad, Taj (Journal of Ayub Medical College Abbottabad, 2017)
Background: Surgical site infection in orthopaedic implants is a major problem, causing long hospital stay, cost to the patient and is a burden on health care facilities. It increases rate of non-union, osteomyelitis, implant failure, sepsis, multiorgan dysfunction and even death. Surgical site infection is defined as pain, erythema, swelling and discharge from wound site. Surgical site infection in orthopaedic implants is more challenging to the treating orthopaedic surgeon as the causative organism is protected by a biofilm over the implant’s surface. Antibiotics cannot cross this film to reach the bacteria’s, causing infection. Method: This descriptive case series study includes 132 patients of both genders with ages between 13 years to 60 years conducted at Orthopaedic Unit, Ayub Medical College, Abbottabad from 1st October 2015 to 31st March 2016. Patients with close fractures of long bones were included in the study to determine the frequency of surgical site infection in orthopaedic implants and the type of bacteria involved and their sensitivity to various antibiotics. All implants were of stainless steel. The implants used were Dynamic hip screws, Dynamic compression screws, plates, k-wires, Interlocking nails, SIGN nails, Austin Moore prosthesis and tension band wires. Pre-op and post-op antibiotics used were combination of Sulbactum and Cefoperazone which was given 1 hour before surgery and continued for 72 hours after surgery. Patients were followed up to 4 weeks. Pus was taken on culture stick, from those who developed infection. Results were entered in the pro forma. Results: A total of 132 patients of long bone fractures, who were treated with open reduction and internal fixation, were studied. Only 7 patients developed infection. Staphylococcus Aureus was isolated from all 7 patients. Staphylococcus aureus was sensitive to Linezolid, Fusidic Acid, and vancomycin. Cotrimoxazole, tetracycline, Gentamycin and Clindamycin were partially effective. Conclusion: Surgical Site Infection is common in orthopaedic implants, occurring in 5.30% cases. Staphylococcus aureus is the common bacteria, causing it. Keywords: Surgical site infection; Orthopaedic implants; Open reduction internal fixation; Close fracture